The mind, the narrative, and the city: how narratives of space make place in cognitive maps - Kellams, Timothy Rossiter (Kansas State University, 2017)
Narratives of urban experiences influence understanding of space and urban form. Narratives give meaning to space, creating memories of places and helping to define an individual’s cognitive map. The representation of narratives within cognitive maps impacts day to day activities, as well as, emotional, cultural, and social characteristics of one’s self. Planners and designers play an important role in crafting narratives through the implementation of designs and policies that together shape urban form. This research investigates the relationship between spatial cognitive schemas and narratives within cognitive maps. Specifically, how college students develop and use narratives within their cognitive map to help with living in a new and initially unfamiliar place of residence. Through mixed method analysis of drawn individual cognitive maps, an online survey, and a group discussion, results show that different types of experiences within narratives influence the likelihood of it appearing within the spatial cognitive schema. The findings suggest that narratives created by peak emotional experiences contain a longer and clearer representation within cognitive maps because of their personal value. By better understanding the role of these emotional responses and their connection with urban form, design professionals can aim to frame projects toward influencing individual’s lives. Understanding how individuals develop narratives of their new city may influence planning and design with the goal of creating urban projects that provide social and cultural significance through meaning of place.
Keywords: Narratives; Spatial cognitive schemas; Experience; Urban form; Map visualizationCognitive maps